A non-normal framework for price discovery: The Independent Component based Information Shares measure - Sebastiano Michele Zema (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2023)
I propose a new measure of price discovery, which I will refer to as the Independent Component based Information Share (IC-IS). This measure constitutes a variant of the widespread Information Share, with the main difference being it does not suffer the same identification issues. Under the assumptions of non-normality and independence of the shocks, a rather general theoretical framework leading to the estimation of the IC-IS is illustrated. After testing the robustness of the proposed measures to different non-Normal distributions in a simulated environment, an empirical exercise encompassing different price discovery applications will follow.
Keywords: C32; C58; G14; 330; Vector error correction models (VECMs); information shares; market microstructure; independent component analysis; pseudo maximum likelihood; price discovery